Clinical relevance of biomarkers in cholangiocarcinoma: critical revision and future directions. Issue 8 (17th May 2022) - Macias, Rocio I R; Cardinale, Vincenzo; Kendall, Timothy J; Avila, Matias A; Guido, Maria; Coulouarn, Cedric; Braconi, Chiara; Frampton, Adam E; Bridgewater, John; Overi, Diletta; Pereira, Stephen P; Rengo, Marco; et al.
Abstract : Cholangiocarcinoma (CCA) is a malignant tumour arising from the biliary system. In Europe, this tumour frequently presents as a sporadic cancer in patients without defined risk factors and is usually diagnosed at advanced stages with a consequent poor prognosis. Therefore, the identification of biomarkers represents an utmost need for patients with CCA. Numerous studies proposed a wide spectrum of biomarkers at tissue and molecular levels. With the present paper, a multidisciplinary group of experts within the European Network for the Study of Cholangiocarcinoma discusses the clinical role of tissue biomarkers and provides a selection based on their current relevance and potential applications in the framework of CCA. Recent advances are proposed by dividing biomarkers based on their potential role in diagnosis, prognosis and therapy response. Limitations of current biomarkers are also identified, together with specific promising areas (ie, artificial intelligence, patient-derived organoids, targeted therapy) where research should be focused to develop future biomarkers.